2014
DOI: 10.1080/14623943.2014.969696
|View full text |Cite
|
Sign up to set email alerts
|

The impact of transformative learning in a critical service-learning program on teacher development: building a foundation for inclusive teaching

Abstract: With international and national policies requiring teachers to adopt inclusive practices worldwide, this paper examines the impact of transformational learning in a critical service-learning program on final-year pre-service teachers' approaches to inclusive teaching. Data from emailed questionnaires and focus group interviews are analysed through a social, critical framework. The results indicate that the critical service-learning program provided the students with an opportunity to consider diversity and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 11 publications
1
16
0
8
Order By: Relevance
“…1 (see e.g., Burner and Biseth 2016). Inclusive teaching involves developing a learning environment whereby all students not only have the right to access all learning activities but are in reality included within class discussions and democratic activities in the school community (Carrington et al 2015;Biseth 2010). This requires teachers to develop a deep knowledge of their students' backgrounds and for them to be able to analyze the reasons for difficulties in accessing democratic activities and having their say in the classroom (Ainscow et al 2006).…”
Section: Inequalities and Learning Political Engagementmentioning
confidence: 99%
“…1 (see e.g., Burner and Biseth 2016). Inclusive teaching involves developing a learning environment whereby all students not only have the right to access all learning activities but are in reality included within class discussions and democratic activities in the school community (Carrington et al 2015;Biseth 2010). This requires teachers to develop a deep knowledge of their students' backgrounds and for them to be able to analyze the reasons for difficulties in accessing democratic activities and having their say in the classroom (Ainscow et al 2006).…”
Section: Inequalities and Learning Political Engagementmentioning
confidence: 99%
“…Asimismo, cabe destacar la capacidad del alumnado para adoptar un enfoque más inclusivo en sus sesiones. A través del ApS el alumnado ha evidenciado un desarrollo de sus competencias relativas a la inclusión (Carrington et al, 2015;) y la diversidad (Cámara et al, 2017;Mergler et al, 2017).…”
Section: Discusión Y Conclusionesunclassified
“…Este logro concuerda con los resultados generales presentados por Celio et al (2011) con los de Houshmand Spanierman, Beer, Poteat y Lawson (2014) en su estudio sobre actitudes intolerantes, y también con los de Chang et al (2011) en su análisis en ámbitos multiculturales. En la misma línea, Peralta et al (2016) indican que el alumnado universitario ve incrementada su competencia y conocimiento cultural, mientras que Carrington et al (2015) y Warren (2012) afirman que el ApS se erige como una forma óptima de ayudar al alumnado a concebir qué constituye una realidad multicultural. A la luz de estos resultados, puede destacarse la importancia de la diversidad como elemento modulador del aprendizaje cultural del alumnado.…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation
“…They then review the main phases of the course project from (1) identifying the social and environmental dilemma, to (2) designing and developing a social business plan, to (3) implementation and mobilization of resources to jumpstart the project, and finally reflect on experiences and learning outcomes. In the process, the authors argue for the role of professors in these international ventures, as very few studies, if any, emphasize the importance of professors' learning experiences (Carrington et al, 2015). It is reported that professors undergo what is then labeled a process of 'reflexivity', which can be related to lived experience and its impact on reality (Godfrey et al, 2005), as well as involving an understanding of how their decisions shape a program and its consequences (Hardy et al, 2001), and how they influence students' ability to be critical.…”
Section: Discourse Of Innovation: Radical Integrationmentioning
confidence: 99%